Effects of Depot Medroxyprogesterone Acetate Intramuscular Injection, Copper Intrauterine Device and Levonorgestrel Implant Contraception on Estradiol Levels: An Ancillary Study of the ECHO Randomized Trial - Ryan, Rebecca; Mussa, Aamirah; Singtaa-Madliki, Mandisa; Batting, Joanne; Balakrishna, Yusentha; Morroni, Chelsea; Hofmeyr, G. Justus (Frontiers in Global Women's Health, 2022)
Introduction Hormonal contraception affects endogenous sex steroid levels. Robust evidence from randomized trials of the relative effects of different contraceptive methods is scarce. We compared the effects of three contraceptive methods on serum estradiol levels using data from women (18–35 years) requesting contraception in the Evidence for Contraceptive Options and HIV Outcomes (ECHO) randomized trial. Methods Women were randomly allocated to the depot medroxyprogesterone acetate intramuscular (DMPA-IM) injection, copper intrauterine device (IUD) or levonorgestrel (LNG) implant. In this sub-study, stored baseline and 6-month serum samples were analyzed in 401 participants from East London, South Africa (DMPA-IM: 131, IUD: 135 and LNG: 135). Results Baseline median (interquartile range, IQR) estradiol levels were similar between the three groups [DMPA-IM 229 (152–455), IUD 235 (168–426) and LNG 216 (153–419 pmol/L)]. At 6-months, median estradiol in the IUD group was unchanged (298 (163–467) pmol/L), whilst levels in the DMPA-IM and implant groups were significantly reduced from baseline. The median estradiol level in the DMPA-IM group [139 (97–193) pmol/L] was significantly lower than in both IUD (p < 0.0001) and implant (p = 0.005) groups; and level in the implant group [156 (112–250) pmol/L] was significantly lower than in the IUD group (p = 0.004). Conclusions At 6-months (DMPA-IM nadir), median estradiol with DMPA-IM was 53% lower and with the LNG implant, 48% lower than with the IUD. The greater reduction in estradiol levels with the DMPA-IM injection compared to the LNG implant and IUD has implications for the relative psychological, sexual as well as physiological side-effects of these contraceptive methods. ECHO Study Registration ClinicalTrials.gov, identifier: NCT02550067.